A Self-Reliance Empowerment Strategy to Improve the Well-Being of the Fishing Community in Kranji Village, Paciran, Lamongan - Anggraeni Rahmasari; Indah Noviandari (Journal Research of Social Science, Economics, and Management, 2026)
The welfare of fishing communities in Kranji Village, Paciran, Lamongan, is strongly influenced by seasonal conditions, limited human resources, and dependence on traditional fishing methods. These conditions contribute to low productivity, unstable income, and continued reliance on middlemen for capital, which ultimately hinders community independence. Therefore, a self-reliance empowerment strategy is needed to improve the socio-economic conditions of the fishing community. This study aims to analyze the implementation of self-reliance empowerment strategies and identify the obstacles faced in improving the welfare of the fishing community in Kranji Village. This research uses a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observations, and documentation involving key informants, including fishermen, capital owners, and village officials. The analysis is based on the empowerment framework consisting of enabling, empowering, and protecting aspects. The results show that the empowerment strategy focuses on strengthening human resource capacity, diversifying productive businesses through fish processing, and providing group-based access to capital. These efforts contribute to improving economic independence, optimizing local potential, and expanding market access. However, the implementation still faces several obstacles, including low education levels, limited skills, dependence culture, lack of access to technology and information, and weak institutional support. The findings imply that sustainable empowerment requires not only financial assistance but also continuous mentoring, capacity building, and strengthening of local institutions. This study contributes both practically and academically by providing insights into